The effect of the triisopropanol amine and triethanol amine mixed additives on the properties of Portland cement - Ta, Ngoc Dung; Pham, Thanh Mai (JST: Engineering And Technology For Sustainable Development, 2022)
The study investigated the effect of a mixture of Triisopropanol amine (TIPA) and triethanol amine (TEA) additives with a mixing ratio of 0.02 ÷ 0.035% on the properties of Portland cement. The study showed that the fineness of cement with the mixture additives is greater than that of cement with the single additive (TIPA+TEA: 2649 cm2/g; TEA: 2601 cm2/g) and they also have the fineness larger than the original cement (2503 cm2/g). The normal consistency tends to increase, the setting time tends to decrease with the additive content in cement samples increases. The compressive strength and the flexural strength at the all days of 1 day or 3, 7, 28 days of cement-additive samples are higher than the original cement. The compressive strength at 1 day of cement-mixture additives sample (0.01% TIPA + 0.02% TEA) is the highest with the level is increased + 24.21%.